Self-Efficacy: Nurses' Perceptions of Caring for Patients Living with Diabetes - Victoria Y. McCue (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2021)
Introduction: Diabetes is an epidemic that affects over 415 million people worldwide. In the United States, the number of people diagnosed with diabetes is projected to triple to over 60 million by 2060. With this surge, the number of hospitalizations across the country has significantly increased. Direct care nurses play a vital role in the management of patients living with diabetes. The purpose of this research study was to explore and describe medical-surgical nurses' perceptions of self-efficacy related to caring for patients living with diabetes. This study's guiding research question was: What are nurses' perceptions on the influences that impact self-efficacy in caring for patients living with diabetes on a medical-surgical unit? Methods: Bandura's Self-Efficacy Theory provided the conceptual framework of this study and guided the development of the interview questions and the analysis of the data. A qualitative descriptive design using a constant comparative analysis method, as described by Strauss and Corbin (1990), was utilized. A purposive, convenience sampling plan was used to recruit eight medical-surgical nurses from two acute care hospitals in the Southeastern United States. Results: Four major themes were revealed in this study: (a) educational preparation, (b) biases towards patients, (c) current clinical environment, and (d) patients' behaviors affect nurses' emotions. Additionally, six subthemes were identified. Discussion: This study's results may inform targeted interventions that promote improved self-efficacy among medical-surgical nurses resulting in optimal patient outcomes for people living with diabetes.